(untitled) (Scientific journal of the Fergana State University, 2024)
This article presents the main characters of Abdukayum Yuldosh’s novel “Timsohning ko`z yoshlari”, their functions in the work, as well as approaches to image and imagery in Uzbek literary criticism. The ideas in the analysis process are based on theoretical data.